Pesticide Reregistration and Special Reviews - Frederick M. Fishel (EDIS)
PI218, a 2-page fact sheet by Frederick M. Fishel, describes the regulations in place to ensure that pesticides are reviewed for health and safety to ensure that they meet current scientific and regulatory standards. Includes additional sources of information. Published by the UF Department of Agronomy, October 2009.